A twin study of rheumatoid arthritis in the Japanese population. Issue 5 (2nd September 2016) - Terao, Chikashi; Ikari, Katsunori; Nakayamada, Shingo; Takahashi, Yusuke; Yamada, Ryo; Ohmura, Koichiro; Hashimoto, Motomu; Furu, Moritoshi; Ito, Hiromu; Fujii, Takao; Yoshida, Shinji; Saito, Kazuyoshi; et al.
Abstract: Objectives : Rheumatoid arthritis (RA) is the most common immune-related inflammatory arthritis affecting 0.5–1.0% of the population. Both genetic and environmental factors are associated with RA onset. Twin studies reported from European countries estimated heritability of RA as 53–65%. However, no twin studies have been reported from Asian countries. Methods : We collected a total of 43 monozygotic and 43 dizygotic twins from 7550 patients with RA and obtained information of RA status in the twin pairs. We characterized RA patients whose twin siblings had RA. Variance components analysis was performed to estimate heritability in RA in the Japanese population. Results : Four and one patients with RA over 43 monozygotic (9.3%) and 43 dizygotic twins (2.3%), respectively, had twin siblings with RA. All the patients whose information of sero-positivity was available and whose twin siblings had RA were sero-positive. Heritability of RA was estimated as 62.2% and 56.1% in the AE and ACE models, respectively. The estimated heritability was comparable with those reported in the Europeans, compatible with previous overlap of RA susceptibility genes between Japanese and European populations. Conclusions : Heritability of RA onset in the Japanese population is estimated to be comparable with that in European populations.